The State of China's State Capitalism Evidence of Its Successes and Pitfalls (Springer Singapore, 2018)
This book comprises a collection of well-researched essays on selected contemporary economic and finance issues in China, making a timely contribution to the intellectual intercourse regarding the implications of China's rise. These essays describe the state of China's ecology, real estate market, outbound capital flows, income inequality, etc., and offer analysis on the policy and institutional causes of those issues. Readers will be able to infer their implications for business opportunities in China and the tradeoff / tension between economic growth and social welfare. Moreover, this book introduces an array of data and data sources useful to scholars and practitioners interested in studying the Chinese model of economic growth. This book will be a valuable resource to journalists and scholars trying to keep track of China's lightning-fast growth. Juann Hung is an Associate Professor at International Business School Suzhou, Xi'an Jiaotong-Liverpool University. She has years of experience as an economist at the Federal Reserve Bank of New York, and then as the lead international analyst at the U.S. Congressional Budget Office. Her research is mainly on policy-related issues, such as effectiveness of foreign exchange intervention, macroeconomic effects of globalization, and the implications of China's growth model. Her research has been published as book chapters, policy and issue briefs, as well as papers in leading research journals. Yang Chen is a Lecturer at International Business School Suzhou, Xi'an Jiaotong-Liverpool University, China. Her research interests mainly include urban economics, Chinese economy and development issues. She has published in leading research journals such as Cambridge Journal of Regions, Economy and Society, Urban Studies, Journal of Regional Science, Economic Letters, International Journal of Finance and Economics, Asia and Pacific Journal of Management, and Economic Modelling.